Development and Implementation of Productivity and Quality Training Programs for the Universities in the Southern Region of Vietnam: VERSION OF RECORD ONLINE: 15/09/2025 - Tran, Thien-Phuc; Nguyen, Thi-Anh-Tuyet; Lai, Huy-Hung; Dang, Hung-Son (Journal of Technical Education Science, 2025)
This paper presents the development process of training productivity and quality programs. These programs are integrated into the compulsory/elective courses in field economics, business, engineering, and technology training programs at the universities in the Southern region of Vietnam. The research uses document research methods, observation, interviews, scientific seminars, and surveys by questionnaires of target groups, as well as the expert method. A Ho Chi Minh City University of Technology case study presents a comprehensive methodology for designing training programs based on a competency framework, implementing and expanding Productivity and quality courses. Based on suggestions, the training program and curriculum framework are visualized. Some critical successes are present, and recommendations are suggested to update and confirm training programs. The training programs will provide essential updates for the teaching staff, allowing them to access the fundamental theoretical basis and general development trends in Productivity and quality. At the same time, the integration of training modules into the training program and closely linked to practice, will help supplement and update the relevant output standards to perfect essential skills, contributing significantly to the success of graduates in the labor market in the context of rapid changes in science and technology of the Fourth Industrial Revolution and the trend of increasingly deep and comprehensive international integration.